A Novel Dual-Rotor Homopolar AC Machine - T. Ruekamnuaychok; J. Zhong; S. Sudhoff; R. Swanson; A. Sah; H. Singh; N. Aronhime; E. Schultz (IEEE Open Access Journal of Power and Energy)
Homopolar AC Machines (HAMs) are of interest because of low rotor loss and the ability to operate at high speeds. These machines are frequently utilized in flywheel energy storage systems but are dominated by permanent magnet or induction machines in other contexts such as vehicle traction. The aim of this work is to explore a new type of homopolar machine. The Dual Rotor Homopolar AC Machine (DHAM) is proposed herein. The fundamental operating principles of the DHAM are explained, and its torque production and terminal characteristics are outlined. The permanent magnet version of the machine is shown to achieve an extended constant power speed range without impacting the PM field intensity, allowing the use of magnet materials with modest values of intrinsic coercive force. The machine includes a modular sectionalized stator, which is easy to wind and cool. The DHAM relies on sinusoidal airgap reluctances, and so the necessary rotor geometry is derived. A prototype machine is used to validate the operating principle.